The migration north - De Medeiros, James, 1975- (Black history (Smartbook Media Inc.), 2020)
Provides a history of Black migration to cities in the Northern United States after slavery ended. Explains the conditions Blacks lived under, discusses the oppression they faced, profiles African American leaders calling for change, and explores ways Blacks tried to make new and better lives for themselves. Includes a timeline, an activity, a quiz, a glossary, and online resources.